Pengaruh Biostimulan dan Pupuk Kandang Sapi Terhadap Produksi Tanaman Cabai Rawit (Capsicum frutescens L.) - Zai, Andi Rahhman; Oesman, Roswita; Dewi, Dora Silvia (UNIVERSITAS LABUHANBATU, 2025)
This study aims to determine the effect of biostimulant and cow manure on the production of cayenne pepper plants (Capsicum frutescens L.). The research problem departs from the fluctuations in cayenne pepper production in North Sumatra, which is influenced by the availability of nutrients in the soil. The study was conducted using a Group Random Design (RAK) with two factors, namely the dose of biostimulants B0 (0 ml/L), B1 (10 ml/L), B2 (15 ml/L) and B3 (20 ml/L) with a dose of cow manure S0 (0 g/polybag), S1 (100 g/polybag), S2 (200 g/polybag) and S3 (300 g/polybag). The observed parameters are production weight per sample and per plot. Data were analyzed using ANOVA and Duncan follow-up test (DMRT) at a confidence level of 5%. The results showed that the interaction of biostimulants and cow manure had a significant effect on the production weight per sample, with the best combination of B1S3 treatment (10 ml/L of biostimulant and 300 g/polybag of cow manure) yielding an average of 103.67 g per sample. Meanwhile, the single application of cow manure had a significant effect on the production weight per plot, with the highest dose of S3 (300 g/polybag) yielding 159.75 g per plot. The conclusion of the results of this study is that the use of a combination of low-dose biostimulants and high-dose cow manure can increase the production of cayenne pepper (Capsicum frutescens L.) plants, significantly compared to no treatment or low doses of cow manure. Keywords: cayenne pepper, biostimulant, cow manure